American property : a history of how, why, and what we own - Banner, Stuart, 1963- (Harvard University Press, 2011)
In this tightly written book, Banner, a professor of law at UCLA, tackles an admittedly expansive topic, illustrating that our ideas about what property is, how it is regulated, and what it is meant to do are in constant flux and have been historically contested. Partly an examination of law, partly of culture, politics, economics, and even religion, Banner successfully shows how our notions of property and so-called "natural property" in essence sketch the shifting borders of what Americans deem appropriate government regulation. "Our conceptions of property have always been molded to serve our particular purposes," Banner writes, using examples ranging from zoning laws (which were often used to enforce racial and economic boundaries); eminent domain and personal property disputes; as well as new, thorny notions of intellectual property in the digital age (digital copying makes some property rights harder to enforce, he notes, but creates new opportunities as well). Banner even addresses biological breakthroughs (can a company own a genetically engineered hybrid or a cell line?). It's a huge amount of history and analysis that ably proves a simple thesis: "the debates have never been about property in the abstract," Banner writes. "Property has always been a means, rather than an end."--Publishers Weekly